2020
DOI: 10.5747/ca.2020.v16.n2.a361
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de cultivares de goiabeiras em ambientes irrigado e sequeiro

Abstract: The fruits of guava (Psidium guajavaL.) are highly appreciated not only for aroma and flavor, but also for nutritional value, being a rich source of vitamin C and can be consumed in naturaor in their industrial forms. The objective of this work was to evaluate the performance of guavacultivars, its initial production and its fruit quality in irrigated and non-irrigated environments. Planting was carried out in February 2016, at 2.0 x 4.5 m spacing, with seedlings forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
1
1
Order By: Relevance
“…According to Cavalini et al (2015), the adequate content of soluble solids for the harvest of 'Paluma' guava is 7.6 °Brix, and the titratable acidity is 0.7%, parameters that were achieved in all treatments of the present study (Figures 6A and B). Martins et al (2020), when evaluating the performance of guava cultivars in irrigated and rainfed environments, found that supplemental irrigation interfered in the total soluble solids content of guava fruits, differing from the present study. Both deficit and excess of water cause stomatal closure as they became stressful factors, thus reducing the absorption of CO 2 , substrate of photosynthesis and, consequently, the production of photoassimilates such as sugars and organic acids (Taiz & Zeiger, 2017).…”
Section: Table 1 Summary Of Analysis Of Variance Of the Variables Ana...contrasting
confidence: 99%
“…According to Cavalini et al (2015), the adequate content of soluble solids for the harvest of 'Paluma' guava is 7.6 °Brix, and the titratable acidity is 0.7%, parameters that were achieved in all treatments of the present study (Figures 6A and B). Martins et al (2020), when evaluating the performance of guava cultivars in irrigated and rainfed environments, found that supplemental irrigation interfered in the total soluble solids content of guava fruits, differing from the present study. Both deficit and excess of water cause stomatal closure as they became stressful factors, thus reducing the absorption of CO 2 , substrate of photosynthesis and, consequently, the production of photoassimilates such as sugars and organic acids (Taiz & Zeiger, 2017).…”
Section: Table 1 Summary Of Analysis Of Variance Of the Variables Ana...contrasting
confidence: 99%
“…Guava (Psidium guajava) is an important tropical fruit species due to the nutritional quality, aroma and flavor of its fruits (Martins et al 2020).…”
Section: Introductionmentioning
confidence: 99%